Intersecting inequities: a scoping review of the gendered relationship between unpaid care work and intimate partner violence during the COVID-19 lockdown in Canada - Alexandra Beukens; Julia Smith (Global Health Action)
Background While there is now extensive research on how COVID-19 lockdowns negatively affected unpaid care burdens and intimate partner violence (IPV), the structural determinants shaping both experiences are less well understood. Objectives The review seeks to answer: how did structural determinants of gender inequality shape both the experiences of increased unpaid care burdens and IPV during the COVID-19 pandemic lockdown? Which policy proposals might mitigate these effects during future pandemic preparedness and response? Methods We conducted a scoping review of two sets of literature: on COVID-19 and unpaid care and COVID-19 on IPV. Following systematic searches of key databases and the application of inclusion/exclusion criteria, we analyzed articles using a gender matrix framework to identify common themes and policy recommendations. Results Common themes include adherence to traditional gender norms, power dynamics featuring coercive control, narrowed pathways to formal and informal supports, and compounding emotional tolls. Policy recommendations from the literature aimed at addressing structural determinants of gender inequality common to both unpaid care and IPV, include expanded access to virtual support services, workplace policies that value the contributions of caregivers, enhanced engagement efforts to incorporate intersectional understandings, and funding for caregiver support services and the anti-violence sector which recognize the value of their contributions. Conclusions Enhanced understanding of the structural determinants of gender inequality at play in experiences of unpaid care work and IPV highlights gaps in pandemic response, which overlooked the role of gender inequities in shaping relationship dynamics, as well as areas for more gender transformative policies.